Checklist of the subfamily Orthocentrinae (Hymenoptera: Ichneumonidae) with seven unrecorded species from Korea - Andrei E. Humala; Jong-Wook Lee; Jin-Kyung Choi (Journal of Asia-Pacific Biodiversity, 2022)
Three genera of Darwin wasps, Entypoma Förster, 1869, Hemiphanes Förster, 1869, and Neurateles Ratzeburg, 1848 are reported for the first time from South Korea. The following seven species, Entypoma robustum Förster, 1871, Hemiphanes erratum Humala, 2007, H. performidatum Rossem, 1988, Neurateles compressus (Thomson, 1897), Plectiscidea (Fugatrix) communis (Förster, 1871), Plectiscidea (P.) undulata Dasch, 1992, and P. (P.) zonata (Gravenhorst, 1829), have been published in the present study. We also provide an updated checklist of Orthocentrinae with new Korean names and photographs of these seven species recently reported for the country.